Adherence to antiretroviral medication in older adults living with HIV/AIDS: a comparison of alternative models - Johnson, Christopher J. (2009)
The CDC estimates that by 2015, half of all persons living with HIV/AIDS in the USA will be over the age of 50. Despite increasing HIV seroprevalence rates in older adults, most research examining adherence to antiretroviral therapy (ART) has focused on young HIV-infected persons and, in general, has been atheoretical in nature. This study examined two ART adherence conceptual frameworks to determine whether these models generalize to HIV-seropositive older adults. Two hundred and forty-four HIV-positive adults 50-plus years of age were recruited through AIDS service organizations in Ohio and New York. Participants completed a neuropsychological battery and an audio computer-assisted self-interview. FIML SEM analyses revealed that neuropsychological functioning was not associated with adherence. Fit indices supported a stress and coping model, with negative affect mediating the effects of social support and maladaptive coping on ART adherence. Results were consistent with stress and coping models and suggest that interventions intending to increase adherence to ART in HIV-infected older adults may be more effective if they address negative affect and enhance adaptive coping and social support.